33.7k views
9 votes
Simplify - 9 - 3 + 7 - 1?

a- 4
b- 5
c- 1
d 5

User Ij
by
4.4k points

2 Answers

2 votes

Answer:

-9-3+7-1

Explanation:

According to order of operations we do this whole thing from left to right!

Solving we get; -9 -3 = -12> -12+7= -5> -5-1 = -6

Lol I got the same answer (ಡ艸ಡ)

User Jatin Parmar
by
4.4k points
6 votes

Answer:

-6

Explanation:

- 9 - 3 + 7 - 1 = - 6

I'm still confused on the answer choices but the expression simplified is equal to -6.

User Dylan Cristy
by
5.2k points